2016
DOI: 10.1002/ece3.2148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating vegetation effects on animal demographics: the role of plant phenology and sampling bias

Abstract: Plant phenological processes produce temporal variation in the height and cover of vegetation. Key aspects of animal life cycles, such as reproduction, often coincide with the growing season and therefore may inherently covary with plant growth. When evaluating the influence of vegetation variables on demographic rates, the decision about when to measure vegetation relative to the timing of demographic events is important to avoid confounding between the demographic rate of interest and vegetation covariates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 45 publications
3
72
1
Order By: Relevance
“…Although no other lesser prairie‐chicken study has reported this threshold relationship, it is consistent with other grouse studies (Wiebe and Martin , McNew et al ). Similarly, nest survival was maximized between 2.0 and 4.0 dm in a quadratic relationship with 75% visual obstruction where visual obstruction was a better predictor of nest survival than vegetation composition; however, this relationship may be biased high because we sampled nest vegetation within 3 days of assessing nest fate, allowing vegetation to grow taller surrounding successful nests (Gibson et al , Smith et al ). Our findings are consistent with those from greater prairie‐chicken ( T. cupido ) research; however, greater prairie‐chicken peak nest survival occurred at a greater visual obstruction, likely because of greater vegetation growth resulting from increased precipitation relative to lesser prairie‐chicken range (McNew et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Although no other lesser prairie‐chicken study has reported this threshold relationship, it is consistent with other grouse studies (Wiebe and Martin , McNew et al ). Similarly, nest survival was maximized between 2.0 and 4.0 dm in a quadratic relationship with 75% visual obstruction where visual obstruction was a better predictor of nest survival than vegetation composition; however, this relationship may be biased high because we sampled nest vegetation within 3 days of assessing nest fate, allowing vegetation to grow taller surrounding successful nests (Gibson et al , Smith et al ). Our findings are consistent with those from greater prairie‐chicken ( T. cupido ) research; however, greater prairie‐chicken peak nest survival occurred at a greater visual obstruction, likely because of greater vegetation growth resulting from increased precipitation relative to lesser prairie‐chicken range (McNew et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that the positive association between grass height, a commonly used metric of herbaceous concealing cover among sage‐grouse nesting studies, and nest survival may be indicative of biased methods rather than a causal relationship (Gibson, Blomberg, et al., ; McConnell et al., ). Using both empirical and simulation approaches, it has been shown that measuring grass height at nests following nest fate (i.e., hatch or failure) produces inflated or even spurious statistical relationships between grass height and nest survival.…”
Section: Introductionmentioning
confidence: 99%
“…We used conditional logistic regression implemented via the clogit function in the package survival (Therneau ) to compare ptarmigan nest or brood use locations (case) to dependent random available locations (control). We were cognizant that vegetation can change over time (i.e., added growth or senescence), and when estimating covariate effects on nest survival, inconsistent timing of measurements can result in biased assessment of those effects on survival (Gibson et al , McConnell et al ). We did not measure vegetation at projected hatch dates as is suggested for nest survival analyses (Gibson et al , McConnell et al ), but we measured vegetation at dependent random sites immediately following measurements at the respective use site (typically within a day or 2 of use), directly comparing vegetation available to females within a given area at that given time (Prima et al ).…”
Section: Methodsmentioning
confidence: 99%